TINJAUAN TERHADAP PERAWATAN KULIT WAJAH WANITA USIA PRODUKTIF DI KELURAHAN BENAI TALUK KUANTAN - Sari, Tri Lanna; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2017)
This research is based of the problem is still the number of women aged 35 years and above (housewife and career woman) who did the facial skin care in Sub Benai Taluk Kuantan. This research is aimed to describe the treatment of facial skin daily and periodic housewife and career woman as well as to analyze the differences of facial skin care daily and periodic housewife and career woman in Sub Benai Taluk Kuantan. This research is descriptive quantitative comparative. The population in this research is a housewife and career woman many as 237 people, the sample is proportional random sampling that samples drawn at random sample of 71 people. Data collection techniques using a questionnaire in the form of Likert scale. The results showed Level of Achievement Respondents in facial skin care everyday housewife in Sub Benai Taluk Kuantan amounted to 70.69% in the medium category, skin care daily facial Career women in Sub Benai Taluk Kuantan amounted to 80.24% with the high category, skin care periodic face housewife in Sub Benai Taluk Kuantan at 59.07% with a bad category, and periodic facial skin care career woman in Sub Benai Taluk Kuantan of 60.51% with a bad category. The results of t test analysis showed for facial skin care everyday there is a difference between Housewives and Career women, while for facial skin care Periodically there is no difference made by the housewife and Career women in Sub Benai Taluk Kuantan, at a significance level of 5 %.Keywords: facial skin care (daily and periodic), Women of childbearing age (housewife and career woman)